Combined Bone Mineral Density (BMD) and Monocyte-to-Lymphocyte Ratio (MLR) Predicts Recurrence and Prognosis in Hepatocellular Carcinoma Patients Following Liver Resection - He ZJ; Hu T; Zhang ZS; Wang TC; Huang W (Dove Medical Press, 2024)
Ze-Jiao He,1,2,* Tao Hu,3,* Zi-Shu Zhang,3 Tian-Cheng Wang,3 Wei Huang3 1Guizhou Medical University, Guiyang, Guizhou, People's Republic of China; 2Department of Radiology, The First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, People's Republic of China; 3Department of Radiology, The Second Xiangya Hospital of Central South University, Changsha, 410011, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei Huang, Department of Radiology, The Second Xiangya Hospital of Central South University, 139 Renmin Middle Road, Changsha, 410011, People's Republic of China, Email 2204150303@csu.edu.cnBackground: Bone mineral density (BMD) and monocyte-to-lymphocyte ratio (MLR) were recently identified as novel risk factors for patients with several malignancies. The objective of this study was to validate the role of preoperative BMD/MLR as a potential prognostic biomarker in patients with hepatocellular carcinoma (HCC) undergoing liver resection.Methods: This investigation enrolled 442 adult patients diagnosed with HCC who underwent liver resection. The patients were classified into high- and low-BMD/MLR groups based on the median, and forward stepwise logistic regression was employed to identify independent predictors for early HCC recurrence. To mitigate the impact of confounding factors, a propensity score matching (PSM) analysis was conducted between patients in the high- and low-BMD/MLR groups. The Kaplan-Meier method was employed to assess and compare the disease-free survival (DFS) and overall survival (OS) between the two cohorts.Results: The study categorized patients into high-BMD/MLR and low-BMD/MLR groups. Forward stepwise logistic regression analysis revealed that low BMD/MLR (P < 0.001), tumor size > 50 mm (P < 0.001), and AFP > 200 ug/L (P = 0.001) were significantly associated with the early recurrence of HCC. Moreover, the results suggested that DFS and OS were significantly shorter in the low-BMD/MLR group compared to the high-BMD/MLR group, both before and after PSM (P < 0.05).Conclusion: Preoperative BMD/MLR held promise as a prognostic biomarker for early recurrence and prognosis in patients with HCC who underwent liver resection. Furthermore, the integration of tumor size, AFP level, and BMD/MLR demonstrated a robust predictive capacity for early recurrence within this patient population.Keywords: hepatocellular carcinoma, resection, bone mineral density, recurrence, prognosis